STRATEGIES FOR DEVELOPING THE DIGITAL ECONOMY - Xudoynazar Ergashev; Alan Karamatdinov; Malikaxon Jumanazarova (Sciental Journals Publishing, 2025)
This article explores various approaches and strategies aimed at fostering the growth and sustainability of the digital economy. It highlights initiatives that leverage digital technologies such as artificial intelligence, blockchain, cloud computing, and the Internet of Things (IoT) to drive innovation, enhance productivity, create new business models, and improve the overall economic landscape. The paper also emphasizes the importance of developing digital infrastructure, investing in digital skills and education, supporting entrepreneurship and innovation ecosystems, strengthening regulatory and cybersecurity measures, and promoting digital inclusion to ensure equitable access to the benefits of the digital economy.
Keywords: Digital innovation, smart cities, e-services, ICT infrastructure, digital literacy, economic growth, digital governance, artificial intelligence, blockchain technology, entrepreneurship